(untitled) (Bangladesh Journal of Agricultural Research, 2008)
India sub continent is a home for aromatic rice diversity. Land races and wild species possess immense potential of most valuable genes which can he effectively utilized in the present day breeding programmes to evolve miracle varieties in rice that possess not high yield potential and quality but also resistant to biotic and abiotic stresses. The present studies were carried out to characterize thirty two aromatic rice accessions of Badshah bhog group from IGKV, Raipur, Chhattisgarh germplasm. These germplasm accessions were evaluated for twenty-two morphological, six agronomical and eight quality characters. The specific genotypes B: 1340, B: 2039, B: 2495, B: 2816, B: 16930 B: 2354, B:1639, B:2094 were identified for quality and agronomical characteristics. These may be used in hybridization programme to achieve desired segregants for good grain quality with higher yield. Key Words: Morphological characters. quality characters, characterization in aromatic rice. doi:10.3329/bjar.v33i3.1607 Bangladesh J. Agril. Res. 33(3) : 479-492, September 2008